Visiting Central and South America - Sardina, Ludivina; Dade County Public Schools, Miami, FL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
This course in Spanish is designed to acquaint the students with the countries of Central and South America and their outstanding historical, cultural, and geographic characteristics. Short stories, pictures, maps, filmstrips, slides, motion pictures, and records are to be used to promote discussions concerning an imaginary trip to these countries. More than 50 activities are prescribed within the scope of the suggested performance objectives. (RL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Area Studies; Audiolingual Skills; Conversational Language Courses; Cultural Education; Educational Objectives; Geographic Regions; Instructional Materials; Language Instruction; Language Skills; Listening Skills; Modern Languages; Reading Skills; Spanish; Teaching Guides; Textbooks; Vocabulary Development; Writing Skills; Central America -- South America